(untitled) (Research, Society and Development, 2020)
Information technology in the different sectors of law, reflects a competitive scenario, in which processes and activities developed by law will reach all professionals working in the area. In this sense, this article gradually describes the stages of the analysis and modeling processes of the development of a website to assist the certification of mandates prepared by bailiffs in Iporá Goiás. Initially, the scope, list of use case list were defined. , use case diagrams, class and relationship entity, system architecture and website prototype. To develop the diagrams, the Astah modeling tool was used for the use case and class diagrams, whereas the relationship entity diagram was used the Workbeanch tool. It is hoped that at the end of the project, it will be possible to assist in the elaboration of the mandate certifications of bailiffs in Iporá Goiás.